Technohumanistic problems through the prism of online translator and interpreter training - Chernovaty, Leonid (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2024)
This paper, which is based on the results of experimental studies of online training of Ukrainian philology students, future interpreters and translators, using machine translation as an example, examines the global and topical issue of balanced coexistence of humans and technology in the context of theoretical ideas of technohumanism. This concept postulates the harmonious and complementary development of humanity and technology. The paper aims to determine the degree of independence and autonomy of a human (student) after having transferred part of their own translation competence to machine translation systems (MT) in the context of online learning, as well as the impact of such transfer on the efficiency of the relevant activity (translation and interpreting). It is established that a significant number of online university students constantly apply MT in their learning activities, including written and oral assignments, even in cases where the conditions of their performance explicitly prohibit it. In the course of studying the ways of concealing the application of MT in oral and written translation, the author has identified a number of methods used by students for this purpose. It is concluded that shifting responsibility for the quality of translation or interpreting to technology as a result of excessive application of MT does not justify itself. In addition, it hinders the development of human translation competence, largely turning it into a supplement to technological tools. Negatively assessing such trends in online specialist training, the author proposes a number of measures to ensure the parallel but more harmonious development of the technology-related and anthropomorphic constituents of the future translator’s and interpreter’s professional competence.